What do outlet's and provider's characteristics mean for family planning consumers? A comparative study of Kenya, Nigeria and Uganda - Truc Ngoc Hoang Dang; Duc Dung Le; Sutthida Chuanwan; Duah Dwomoh (BMC, 2023)
Abstract Background This research investigated the determinants of the number of family planning consumers in Kenya, Nigeria and Uganda, with a focus on outlet's and provider's characteristics which are important factors influencing the choice of using contraceptive methods but largely unexplored in previous literature. Methods We utilized a unique panel survey on outlet's in Kenya (n = 1,321), Nigeria (n = 1,255) and Uganda (n = 842), which is part of the Consumer Market for Family Planning conducted in between 2019 and 2020, for the analysis of the pooled data (n = 3,418) and individual country. Random effects Poisson regressions were performed. Results The pooled data results showed that the expected number of consumers were significantly lower in Nigeria and Uganda than in Kenya, and that working experience (provider's characteristics), types of stores, duration of providing family planning services, participations in community outreach and host community events, and sign of family planning services (outlet's characteristics) were significant determinants of the number of customers. The results for each country revealed interesting similarities and differences in the determinants across the three countries. Conclusions This study sheds light on the relationship between the number of family planning customers and outlet's and provider's characteristics, thus providing informative evidence-based to on-going debates on the coverage of family planning services, which is still insufficient in developing countries. As a result, the government's family planning expenditures should instead prioritize small, private enterprises such as pharmacies or drug stores. Furthermore, it is critical to focus on several critical tasks to improve the qualities of outlets and providers to attract customers, such as ensuring that they are eye-catching, advertising FP services, have professional credentials, fulfil providers' obligations to counsel contraceptive users, provide long-term services and community care, and have female providers.